2019
DOI: 10.1111/jrh.12359
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐Related Beliefs and Perceptions in Appalachia: Findings from 3 States

Abstract: Background:Appalachians experience increased rates of cancer incidence and mortality compared to non-Appalachians. Many factors may contribute to the elevated cancer burden, including lack of knowledge and negative beliefs about the disease. Methods: Three National Cancer Institute (NCI)-designated cancer centers with Appalachian counties in their respective population-based geographic service areas-Kentucky, Ohio, and Pennsylvania-surveyed their communities to better understand their health profiles, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Similar to previous studies from the United States, which have relied on items from HINTS, we also found SES differences in negative cancer beliefs 11,16,23–26 . Though HINTS is also a population‐based survey of US adults, the cancer belief items are distinct, and the results for similar items provide different conclusions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to previous studies from the United States, which have relied on items from HINTS, we also found SES differences in negative cancer beliefs 11,16,23–26 . Though HINTS is also a population‐based survey of US adults, the cancer belief items are distinct, and the results for similar items provide different conclusions.…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge, previous US studies examining SES differences in cancer beliefs have, to date, examined negative beliefs, and relied on items from the Health Information National Trends Survey (HINTS), which focuses on beliefs about cancer prevention 11,16,23–26 . It is therefore unknown whether the results from the United Kingdom and Denmark are applicable to the United States, which has a different healthcare system and different recommendations for early detection and access to health care.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason is racial disparity regarding cancer treatment in PA, which could impact quality of healthcare and physician-patient communications [11,12]. Other contributing factors include limited access to healthcare and PC screening, low socioeconomic status, environmental or occupational exposure to heavy metals, participation in unhealthy lifestyle behaviors (i.e., cigarette smoking and lack of physical activity), and variation in cancer beliefs and perceptions [13][14][15][16]. Therefore, it is recognized that analyzing PCspecific mortality is a multifactorial process that involves the assessment of interactions amongst patients, providers and healthcare facilities, and their communities.…”
Section: Introductionmentioning
confidence: 99%
“…12 Finally, fatalistic beliefs about cancer prevention efforts among rural residents and its negative impact on HPV vaccination have also been cited as contributing factors. [13][14][15] There are limited data examining differences in HPV vaccination coverage by MSA status, particularly among adolescents not initiating the HPV vaccine series. A 2014 analysis noted lower coverage for ≥1 dose of HPV vaccine among adolescents living in other areas when compared to those living in mostly urban areas.…”
Section: Introductionmentioning
confidence: 99%